Submerged arc welding method and method for manufacturing welded joint
Patent Information
- Application Number
- JP2023035369
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-03-08
AI Technical Summary
【0015】 本発明によれば、780MPa級鋼材の入熱300kJ/cm以上の大入熱サブマージアーク溶接方法において、溶接欠陥の発生がなく、溶接金属の630MPa以上の0.2%耐力と780MPa以上の引張強度が得られる。さらに、0℃におけるVノッチシャルピー衝撃試験の吸収エネルギーvE0が27J以上を確保でき、産業上特段の効果を奏する。
Smart Images

Figure 0007637710000001 
Figure 0007637710000002 
Figure 0007637710000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a submerged arc welding method and a method for manufacturing a welded joint, and in particular to a submerged arc welding method for 780 MPa class high tensile steel used for architectural structures with a welding heat input of 300 kJ / cm or more, and a method for manufacturing the welded joint. [Background technology]
[0002] In recent years, the trend toward larger and longer span architectural structures has led to a trend toward higher strength steel plates used in steel frames. Conventionally, the strength class of steel for skin plates in box columns was mainly up to 590 MPa, but 780 MPa class steel is now being used.
[0003] Submerged arc welding is generally used to join skin plates of box columns, and the strength of the weld metal is required to have strength characteristics equivalent to that of the base material. As a welding material for submerged arc welding that can ensure a weld metal strength of 780 MPa or more, for example, Patent Document 1 discloses a solid wire for submerged arc welding. This document describes that the contents of C, Si, Mn, Ni, Cr, Mo, P, and S in the wire are specified, and that ([Mn] + [Ni]) / ([Cr] + [Mo]) is adjusted to 1.4 to 4.0. It is said that this can significantly improve the low-temperature toughness and hydrogen embrittlement susceptibility of the weld metal.
[0004] Patent Document 2 discloses a submerged arc welding method for 780 MPa-class high-tensile steel, and describes how a good bead shape without slag inclusion can be obtained by optimizing the amount of alloy elements in the sintered flux and the particle size of the flux. It also describes how a weld metal with high strength and good low-temperature toughness, with a tensile strength of 780 MPa or more, can be obtained by limiting the chemical composition of the solid wire to be combined.
[0005] Patent Document 3 discloses a wire for double-sided, single-layer submerged arc welding. In double-sided, single-layer submerged arc welding, which involves large dilution of the base metal, the wire composition is limited to ensure the strength and toughness of the weld metal, and the tensile strength of the wire is increased to 1200 N / mm 2 It is said that wire feedability can be ensured by limiting the following:
[0006] Furthermore, Patent Document 4 discloses a high-strength welded steel pipe manufactured by performing submerged arc welding on both the inner and outer surfaces, one layer at a time, in which the tensile strengths of the base material and weld metal are both 800 MPa or more, and the weld metal has excellent resistance to low-temperature cracking. It is said that by specifying the CS value calculated from the contents of Mo, Ni, Mn, and C, a weld metal with excellent resistance to low-temperature cracking can be obtained. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2015-110241 A [Patent Document 2] JP 2015-120175 A [Patent Document 3] JP 2004-337863 A [Patent Document 4] JP 2008-240096 A Summary of the Invention [Problem to be solved by the invention]
[0008] The welding heat input applied in Patent Documents 1 to 4 is 50 kJ / cm or less. In the manufacture of box columns in which a steel material of 590 MPa class or less is used for the skin plate, submerged arc welding with a welding heat input (hereinafter also simply referred to as "heat input") of more than 300 kJ / cm is generally applied from the viewpoint of construction efficiency.
[0009] However, when the welding materials disclosed in Patent Documents 1 to 4 are used and applied with a heat input of 300 kJ / cm or more, problems such as the occurrence of welding defects, insufficient strength of the weld metal, and deterioration of toughness occur.
[0010] An object of the present invention is to solve the above-mentioned problems and to provide a submerged arc welding method that is capable of producing a welded joint that is free of welding defects and satisfies the required yield strength, tensile strength, and toughness, even when submerged arc welding is performed with a heat input of 300 kJ / cm or more.
[0011] The required strength of the weld metal here means that the room temperature yield strength (0.2% proof stress) of the weld metal prepared in accordance with the provisions of JIS Z 3111 is 630 MPa or more, and its tensile strength is 780 MPa or more. The required toughness of the weld metal means the absorbed energy of a V-notch Charpy impact test at a test temperature of 0°C for the weld metal of a welded joint prepared in accordance with the provisions of JIS Z 3128. v This means that E0 is 27J or more. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that in a submerged arc welding method with a heat input of 300 kJ / cm or more, it is effective to set the CeqW of the welding wire (hereinafter, simply referred to as the "wire") represented by the formula (1) described below to 0.40 to 0.80 in order to prevent the occurrence of welding defects.
[0013] However, if the CeqW of the welding wire is 0.80 or less, when it is combined with a conventional flux for submerged arc welding, the problem of insufficient strength of the weld metal cannot be solved. It has been found that to solve this problem, it is effective to add an element effective for improving the strength of the weld metal from the flux and adjust α represented by the formula (2) described later to 0.35 to 0.70.
[0014] The present invention was completed based on these findings and through further investigation, and the gist of the present invention is as follows. [1] In a submerged arc welding method for 780MPa class steel with a welding heat input of 300kJ / cm or more, The chemical composition of the welding wire used is, in mass%, C: 0.03% to 0.12%, Si: 0.01% to 0.60%, Mn: 1.0% to 2.0%, P: 0.015% or less, S: 0.015% or less, Ni: 1.0%~4.0%, Cr: 1.5% or less, Mo: 0.2% to 1.2%, O: 0.015% or less, N: 0.010% or less, The remainder is Fe and unavoidable impurities, CeqW represented by the following formula (1) is in the range of 0.40 to 0.80, The composition of the flux used is, in mass%, SiO2: 5%~30%, CaO: 1% to 10%, MgO: 5% to 30%, Al2O3: 3%~20%, TiO2: 2%-20%, Na2O: 1% to 3%, CaF2: 2%-20%, Total of CO2 equivalent value of one or more metal carbonates: 2% to 12% Si: 0.10% to 2.50%, Mn: 0.1% to 2.0%, Ni: 1.0%~12.0%, Cr:8.0% or less, Mo: 1.0%~8.0%, Fe: 10%~30%, Contains The value of α represented by the following formula (2) is in the range of 0.35 to 0.70. A submerged arc welding method comprising: CeqW=[C]W +[Si] W / 24+[Mn] W / 6+[Ni] W / 40+[Cr] W / 5+[Mo] W / 4 ··· (1) α = (0.3-[Fe] F / 200)×{[Si] F / 24+[Mn] F / 6+[Ni] F / 40+[Cr] F / 5+[Mo] F / 4}+0.4×CeqW ··· (2) Here, the [elements] of the wire in the above formula (1) W Or the [component] of the flux in the above formula (2) F indicates the content (mass%) of the element or component, and if the element or component is not contained, it is set to 0. [2] In the above [1], in addition to the chemical composition of the welding wire, Cu: 1.0% or less, Al: 0.20% or less, Ti: 0.20% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.010% or less, B: 0.010% or less, REM: 0.020% or less A submerged arc welding method comprising the steps of: [3] In the above [1] or [2], in addition to the component composition of the flux, B2O3: 1.0% or less, K2O: 3.0% or less, Ti: 1.00% or less, Al: 1.00% or less A submerged arc welding method comprising the steps of: [4] A method for manufacturing a welded joint, characterized in that the welded joint is manufactured using the submerged arc welding method described in any one of [1] to [3] above. [5] In the above [4], the chemical composition of the weld metal of the weld joint is, in mass%, C: 0.04%~0.10%, Si: 0.10% to 0.80%, Mn: 0.9% to 2.0%, P: 0.015% or less, S: 0.015% or less, Ni: 1.6%~5.0%, Cr: 0.3%~2.0%, Mo: 0.5% to 2.0%, O: 0.040% or less, N: 0.010% or less, The remainder is Fe and unavoidable impurities, CeqD represented by the following formula (3) is 0.75 to 0.95 A method for manufacturing a welded joint comprising the steps of: CeqD=[C] D +[Si] D / 24+[Mn] D / 6+[Ni] D / 40+[Cr] D / 5+[Mo] D / 4 ··· (3) Here, the [elements] of the weld metal in formula (3) D indicates the content (mass%) of the element, and if the element is not contained, it is set to 0. [6] In the above [5], in addition to the chemical composition of the weld metal of the weld joint, Cu: 1.0% or less, Al: 0.12% or less, Ti: 0.12% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.010% or less, REM: 0.020% or less A method for manufacturing a welded joint, comprising the steps of: [7] In the above [5] or [6], the mechanical properties of the weld metal of the welded joint are such that the yield strength (0.2% proof stress) at room temperature is 630 MPa or more, the tensile strength of the weld metal is 780 MPa or more, and the absorbed energy in a V-notch Charpy impact test at a test temperature of 0°C is V A method for manufacturing a welded joint, characterized in that E0 is 27J or more. Effect of the Invention
[0015] According to the present invention, in a high heat input submerged arc welding method with a heat input of 300 kJ / cm or more for 780 MPa class steel, no welding defects are generated and the weld metal has a 0.2% proof stress of 630 MPa or more and a tensile strength of 780 MPa or more. Furthermore, the absorbed energy in a V-notch Charpy impact test at 0°C is v E0 of 27J or more can be ensured, which is of particular benefit to the industry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be specifically described.
[0017] The present invention relates to a submerged arc welding method using specific welding materials (welding wire and flux) for 780 MPa class steel. First, the submerged arc welding will be described.
[0018] [Submerged arc welding] Submerged arc welding is a welding method in which an electrode wire is continuously fed into powder-like flux that has been spread on the base metal in advance, and an arc is generated between the tip of the electrode wire and the base metal to perform continuous welding. This submerged arc welding has the advantage that it can be efficiently performed by applying a large current to increase the wire deposition speed.
[0019] The wire may be a solid wire or a flux-cored wire containing flux for wire inside the wire. In the present invention, welding is performed using a solid wire having the component composition described below.
[0020] As an example of the high heat input submerged arc welding according to the present invention, steel materials are butted together, a 35° V groove is formed, flux is spread using a prepared solid wire (diameter 6.4 mmφ), and then welding is performed in a downward position with leading and trailing electrodes under the following conditions: current: 1400 A to 2200 A (AC), voltage: 36 V to 50 V, welding speed: 16 cm / min to 30 cm / min, welding heat input: 300 kJ / cm to 700 kJ / cm.
[0021] The groove is prepared so that the steel plates to be welded together form a predetermined groove shape. The groove shape to be formed does not need to be particularly limited, and examples of the groove shape include a V groove, a L groove, an X groove, and a K groove, which are typical grooves for welded steel structures. In addition, the groove angle of a typical V groove is preferably 20° to 45°.
[0022] Furthermore, although the submerged arc welding is intended to be a one-pass submerged arc welding, in the case of steel materials with a large plate thickness, multi-layer welding of two or more passes can also be used.
[0023] Under the above submerged arc welding conditions, 780 MPa class steel as the base material is butted together, and a welded joint is produced using the welding wire and flux described below.
[0024] [Basic composition of welding wire] In order to ensure the strength of the weld metal in 780MPa-class submerged arc welding, it is effective to add elements that contribute to improving strength, such as C, Si, Mn, Ni, Cr, and Mo, from the welding wire, and the welding wire must have a CeqW of 0.40 or more, as expressed by formula (1) described below. However, if CeqW exceeds 0.80, the wire becomes too hard, which deteriorates wire feedability and leads to welding defects, so CeqW must be limited to 0.80 or less.
[0025] The basic composition of the welding wire suitable for 780 MPa-class submerged arc welding, which is a feature of the present invention, will be described below. Note that, hereinafter, "%" in the composition means "mass %".
[0026] [C:0.03%~0.12%] C is an element that improves the strength of the weld metal, and has a large influence. If the C content in the wire is less than 0.03%, the weld metal strength is insufficient. On the other hand, if it exceeds 0.12%, a hard second phase is formed in the weld metal, and the toughness is deteriorated. Therefore, the C content is limited to the range of 0.03% to 0.12%, preferably 0.04% to 0.10%, and more preferably 0.05% to 0.09%.
[0027] [Si: 0.01%~0.60%] Silicon acts as a deoxidizing element in the weld metal and reduces the amount of dissolved oxygen, thereby contributing to improving the toughness of the weld metal. It also has the effect of increasing strength by lowering the transformation temperature. For this reason, the content is limited to 0.01% or more. On the other hand, if the content exceeds 0.60%, it promotes the formation of a hard second phase in the weld metal, deteriorating the toughness. For this reason, the content of silicon is limited to the range of 0.01% to 0.60%. The content is preferably 0.02% to 0.50%, and more preferably 0.04% to 0.40%.
[0028] [Mn: 1.0%~2.0%] Mn is an element that enhances hardenability, and in order to ensure the strength of the weld metal, a content of 1.0% or more is required. On the other hand, since it is an element that is prone to solidification segregation, if the content exceeds 2.0%, hot cracking is induced by solidification segregation. Therefore, Mn is limited to 1.0% to 2.0%. It is preferably 1.2% to 1.9%, and more preferably 1.4% to 1.8%.
[0029] [P:0.015% or less] P is an element that segregates at grain boundaries in weld metal and induces hot cracking, so it is preferable to reduce it as much as possible, but 0.015% or less is acceptable. Therefore, P is limited to 0.015% or less. Note that excessive reduction leads to high refining costs, so P is preferably adjusted to 0.003% or more. More preferably, it is 0.005% to 0.012%.
[0030] [S:0.015% or less] S is an element that segregates at grain boundaries in weld metal and induces hot cracking, so it is preferable to reduce it as much as possible, but 0.015% or less is acceptable. Therefore, S is limited to 0.015% or less. However, since excessive reduction leads to high refining costs, S is preferably adjusted to 0.002% or more. More preferably, it is 0.003% to 0.010%.
[0031] [Ni: 1.0%~4.0%] Ni is an effective element for increasing the strength of weld metal without reducing toughness, so the Ni content is set to 1.0% or more. On the other hand, Ni is an austenite stabilizing element, and if it is contained in excess of 4.0%, the solidification primary crystals become austenite phase, which increases solidification segregation and induces hot cracking. Therefore, Ni is limited to 1.0% to 4.0%. It is preferably 1.2% to 3.6%, and more preferably 1.5% to 3.2%.
[0032] [Cr:1.5% or less] Cr is an element effective in improving strength. However, if it is contained in an amount exceeding 1.5%, the strength of the wire becomes too high, and wire feedability during welding deteriorates. Therefore, Cr is limited to 1.5% or less. Furthermore, the effect of improving strength is significant at a content of 0.1% or more, so if Cr is contained, it is preferable that the content be 0.1% or more. More preferably, it is 0.1% to 1.3%.
[0033] [Mo: 0.2%~1.2%] Mo is an element effective in improving strength, and is preferably contained at 0.2% or more. On the other hand, if it is contained at more than 1.2%, the strength of the wire becomes too high, and wire feedability during welding deteriorates. Therefore, Mo is limited to the range of 0.2% to 1.2%, preferably 0.3% to 1.0%, and more preferably 0.4% to 0.9%.
[0034] [O: 0.015% or less] O (oxygen) is an unavoidable impurity that deteriorates wire drawability by forming oxides. Therefore, it is preferable to reduce the O content as much as possible, but since 0.015% or less is acceptable, it is limited to 0.015% or less. It is preferably 0.010% or less, and more preferably 0.001% to 0.008%.
[0035] [N:0.010% or less] N (nitrogen) is an unavoidable impurity that deteriorates the toughness of the weld metal, so it is preferable to reduce the N content as much as possible, but since a N content of 0.010% or less is acceptable, the N content is limited to 0.010% or less, preferably 0.009% or less, and more preferably 0.002% to 0.008%.
[0036] [Optional composition of welding wire] The above-mentioned chemical composition is the basic composition of the welding wire of the present invention, and in addition to this basic composition, the present invention may further contain the following optional compositions as necessary: one or more selected from Cu: 1.0% or less, Al: 0.20% or less, Ti: 0.20% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.010% or less, B: 0.010% or less, and REM: 0.020% or less. Each of these will be explained individually below.
[0037] [Cu:1.0% or less] Cu is an element that finely precipitates in the weld metal and improves strength through precipitation strengthening. However, if it is contained in excess of 1.0%, red brittleness will be observed in the temperature range of about 1100°C, inducing bead surface cracks, so it is preferable to keep it in the range of 1.0% or less. Such a strength improving effect is remarkable at 0.1% or more, so it is more preferable to contain 0.1% or more. It is further preferable to contain 0.1% to 0.8%.
[0038] [Al: 0.20% or less] Al acts as a deoxidizing element in the weld metal, and reduces the amount of dissolved oxygen, thereby reducing oxides and contributing to high toughness of the weld metal. However, if it is contained in excess of 0.20%, it forms coarse Al2O3 in the weld metal, which becomes the starting point of fracture. Therefore, it is preferable to keep it in the range of 0.20% or less. To obtain such a high toughness effect, it is more preferable that Al is contained in an amount of 0.01% or more. More preferably, it is contained in the range of 0.01% to 0.16%.
[0039] [Ti:0.20% or less] Ti acts as a deoxidizing element in the weld metal and reduces the amount of dissolved oxygen. It also reduces the interfacial energy between oxides and molten steel, finely dispersing the oxides and contributing to improving the toughness of the weld metal. However, if it is contained in excess of 0.20%, the amount of dissolved Ti in the weld metal increases, decreasing ductility and toughness. Therefore, it is preferable to keep it in the range of 0.20% or less. To obtain such a toughness improving effect, it is more preferable that Ti is contained in an amount of 0.01% or more. It is further preferable that it is contained in a range of 0.01% to 0.15%.
[0040] [Nb:0.10% or less] Nb is an element that improves hardenability and contributes to improving the strength of the weld metal. However, if it is contained in an amount exceeding 0.10%, the strength of the wire becomes too high, and wire feedability during welding deteriorates. Therefore, the Nb content is preferably in the range of 0.10% or less. To obtain such a strength improving effect, the Nb content is more preferably 0.01% or more. More preferably, the Nb content is 0.02% to 0.08%.
[0041] [V:0.10% or less] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides in the weld metal. However, if it is contained in an amount exceeding 0.10%, the strength of the wire becomes too high, and wire feedability during welding deteriorates. Therefore, it is preferable that the V content is in the range of 0.10% or less. To obtain such a strength-improving effect, it is more preferable that the V content is 0.01% or more. It is further preferable that the V content is 0.02% to 0.08%.
[0042] [Ca:0.010% or less] Ca combines with S to form sulfide (CaS), thereby suppressing hot cracking. However, if it is contained in an amount exceeding 0.010%, it segregates at the prior austenite grain boundaries, embrittling the grain boundaries and thus reducing wire drawability. Therefore, when Ca is contained, it is preferable that the Ca content is in the range of 0.010% or less. In order to obtain such a hot crack suppression effect, it is more preferable that the Ca content is 0.001% or more. More preferably, it is 0.002% to 0.008%.
[0043] [B:0.010% or less] B is an element that enhances hardenability and contributes to improving the strength of the weld metal. However, if it is contained in an amount exceeding 0.010%, it induces hot cracking. Therefore, when B is contained, it is preferable that the content be in the range of 0.010% or less. In order to obtain such a strength improving effect, it is more preferable that B is contained in an amount of 0.001% or more. More preferably, it is contained in the range of 0.002% to 0.008%.
[0044] [REM:0.020% or less] REM combines with S in the molten metal to form sulfides with high melting points, suppressing the formation of sulfides with low melting points and contributing to the suppression of hot cracking. However, if it is contained in excess of 0.020%, it segregates at the prior austenite grain boundaries and embrittles the grain boundaries, resulting in a decrease in wire drawability. Therefore, when REM is contained, it is preferable that the content is 0.020% or less. In order to obtain such a hot crack suppression effect, it is more preferable that the REM content is 0.002% or more. More preferably, the content is 0.003% to 0.015%.
[0045] [Remainder of welding wire composition] The remaining composition other than the above-mentioned composition is composed of Fe and inevitable impurities. Examples of inevitable impurities include Sn, Sb, As, Pb, and Bi. It is preferable that the contents of Sn, Sb, and As in the wire are each 0.005% or less, and the contents of Pb and Bi are each 0.0001% or less. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, it is not prohibited to contain inevitable impurity elements other than these, and such embodiments are also included in the technical scope of the present invention.
[0046] [Welding wire CeqW] As described above, in a submerged arc welding method with a heat input of 300 kJ / cm or more, in order to prevent the occurrence of welding defects, it is effective to adjust the CeqW of the welding wire represented by the following formula (1) to 0.40 to 0.80. CeqW=[C] W +[Si] W / 24+[Mn] W / 6+[Ni] W / 40+[Cr] W / 5+[Mo] W / 4 ··· (1) Here, the [elements] of the wire in formula (1) W indicates the content (mass%) of the element, and if the element is not contained, it is set to 0.
[0047] The reason why the wire CeqW is set to 0.40 or more is to add elements that improve strength from the wire. On the other hand, if the CeqW exceeds 0.80, the wire becomes too hard, the wire feedability deteriorates, and wire feed becomes unstable. This causes the wire feed to stop, the welding to stop, or the wire curl cannot be corrected completely, causing the wire to miss the target position, resulting in unmelted grooves, i.e., welding defects.
[0048] [Wire manufacturing method] Next, a method for producing the welding wire (solid wire) of the present invention will be described. The welding wire of the present invention can be manufactured by any of the conventional manufacturing methods for welding wire.
[0049] For example, the solid wire of the present invention is produced by a casting process in which molten steel having the above-mentioned composition is melted in a conventional melting furnace such as an electric furnace or a vacuum melting furnace, and cast into a mold or the like having a predetermined shape. Next, a heating process in which the obtained steel ingot is heated to a predetermined temperature, and a hot rolling process in which the heated steel ingot is hot rolled to form a steel material (rod-shaped) having a predetermined shape are sequentially carried out. Furthermore, it is preferable to carry out a cold rolling process in which the obtained steel material (rod-shaped) is cold-rolled multiple times (cold wire drawing) and, if necessary, an annealing process at an annealing temperature of 500°C to 900°C to form a wire of the desired dimensions.
[0050] [Flux basic composition] Next, we conducted extensive research into a flux suitable for a welding wire having the above-mentioned composition. As a result, we found that, as described above, it is effective to add an element effective for improving the strength of the weld metal from the flux and adjust α, expressed by the formula (2) described below, to 0.35 to 0.70 in order to solve the problem of insufficient strength of the weld metal. The basic composition of the flux (compound composition + metal composition) is described below. In the following, "%" in the composition means "mass %".
[0051] [Compound composition in basic composition of flux] [SiO2:5%~30%] SiO2 is an important component for forming a good weld bead, and if the SiO2 content is less than 5%, the bead toe will not fit well and undercut will occur. On the other hand, if the SiO2 content exceeds 30%, the oxygen content of the weld metal will increase and the toughness will deteriorate. Therefore, the SiO2 content is limited to 5% to 30%. It is preferably 8% to 25%.
[0052] [CaO: 1%-10%] CaO has the effect of adjusting the melting point and fluidity of the slag. If it is less than 1%, the bead toe does not conform well and undercut occurs. On the other hand, if it exceeds 10%, the fluidity is poor, the bead height becomes non-uniform, the bead appearance is deteriorated, and the slag removability is also deteriorated. Therefore, the CaO content is limited to 1% to 10%. It is preferably 2% to 8%.
[0053] [MgO: 5%~30%] MgO has the effect of improving the basicity of the slag and reducing the oxygen content of the weld metal, and if it is less than 5%, the oxygen content of the weld metal increases and the toughness deteriorates. On the other hand, if it exceeds 30%, the softening point of the flux increases, the bead height becomes non-uniform, the bead appearance deteriorates, and the slag removability also deteriorates. Therefore, the MgO content is limited to 5% to 30%. It is preferably 8% to 25%.
[0054] [Al2O3: 3%~20%] Al2O3 is a necessary component for obtaining good slag removability and bead appearance, and also has the effect of improving arc stability. To obtain such an effect, the content must be 3% or more. On the other hand, if it exceeds 20%, the viscosity of the flux increases, resulting in a convex bead and poor slag removability. Therefore, the content of Al2O3 is limited to 3% to 20%, and preferably 5% to 18%.
[0055] [TiO2: 2%~20%] TiO2 is a component that contributes to the removability and low-temperature toughness of molten slag, and also has the effect of improving the weld bead shape. To obtain such an effect, a content of 2% or more is required. On the other hand, if the content is 20% or more, the melting point of the molten slag increases too much, and the slag removability deteriorates. Therefore, the TiO2 content is limited to 2% to 20%. Preferably, it is 3% to 18%.
[0056] [Na2O: 1%~3%] Na2O is a component that stabilizes the arc during welding, and in order to obtain this effect, a content of 1% or more is required. On the other hand, if the content is 3% or more, the moisture absorption resistance deteriorates and the amount of diffusible hydrogen in the weld metal increases, inducing low-temperature cracking. Therefore, the Na2O content is limited to 1% to 3%, and preferably 1% to 2%.
[0057] [CaF2: 2%~20%] CaF2 has the effect of lowering the melting point and viscosity of molten slag, and is an effective component for keeping the bead smooth under welding conditions with large heat input. It also reduces the amount of O (oxygen) in the weld metal and improves toughness. To obtain such effects, a CaF2 content of 2% or more is required. On the other hand, if the CaF2 content exceeds 20%, the viscosity of the molten slag becomes too low, inducing undercut and deteriorating slag removability. Therefore, the CaF2 content is limited to 2% to 20%. It is preferably 4% to 18%.
[0058] [Total of CO2 equivalent value of one or more metal carbonates: 2% to 12%] CO2 generated during welding from metal carbonates such as calcium carbonate (CaCO3) and magnesium carbonate (MgCO3) has the effect of insulating the weld metal from the atmosphere and stabilizing the arc. To obtain such an effect, a content of 2% or more is required. On the other hand, if it exceeds 12%, the amount of gas becomes excessive, causing blow-up and deteriorating welding workability. Therefore, the total of the CO2 equivalent value of one or more metal carbonates is limited to 2% to 12%. It is preferably 3% to 10%.
[0059] In addition to the above, other examples of metal carbonates include potassium carbonate (K2CO3), sodium carbonate (Na2CO3), barium carbonate (BaCO3), and lithium carbonate (Li2CO3).
[0060] [Metal composition in the basic composition of the flux] [Si:0.10%~2.50%] Si is added as metal Si, Fe-Si alloy, etc., and acts as a deoxidizer to reduce the oxygen content in the weld metal. It also has the effect of improving the hardenability of the weld metal. To obtain such an effect, a content of 0.10% or more is required. On the other hand, if the Si content exceeds 2.50%, the strength of the weld metal becomes excessive and the toughness deteriorates. Therefore, the Si content is limited to 0.10% to 2.50%, and preferably 0.30% to 2.00%.
[0061] [Mn: 0.1%~2.0%] Mn is added as metal Mn or an Fe-Mn alloy, and acts as a deoxidizer to reduce the amount of oxygen in the weld metal. It also has the effect of improving the hardenability of the weld metal. To obtain such an effect, a content of 0.1% or more is required. On the other hand, if the Mn content exceeds 2.0%, the strength of the weld metal becomes excessive and the toughness deteriorates. Therefore, the Mn content is limited to 0.1% to 2.0%, and preferably 0.2% to 1.8%.
[0062] [Ni: 1.0%~12.0%] Ni is added as metallic Ni, Fe-Ni alloy, etc., and is an important element for improving the strength and toughness of weld metal. To obtain such an effect, a content of 1.0% or more is required. On the other hand, if the Ni content exceeds 12.0%, the solidification primary crystal becomes an austenite phase, which causes large solidification segregation and hot cracking. Therefore, the Ni content is limited to 1.0% to 12.0%, and preferably 2.0% to 10.0%.
[0063] [Cr:8.0% or less] Cr is added as metal Cr, Fe-Cr alloy, etc., and is an element that improves the strength of the weld metal. However, if it exceeds 8.0%, it hardens the weld metal, reducing its toughness. Therefore, the Cr content is limited to 8.0% or less. In addition, the effect of improving the strength is significant at a content of 0.1% or more, so it is preferably in the range of 0.1% to 8.0%. More preferably, it is 0.2% to 7.5%.
[0064] [Mo: 1.0%~8.0%] Mo is added as metal Mo, Fe-Mo alloy, etc., and is an important element for improving the strength of weld metal. To obtain such an effect, a content of 1.0% or more is required. In addition, since Mo is a ferrite stabilizing element, even when Ni is added, it has the effect of maintaining the solidification primary crystal in the ferrite phase and preventing hot cracking. On the other hand, if the Mo content exceeds 8.0%, the weld metal becomes too hard, and the toughness decreases. Therefore, the Mo content is limited to 1.0% to 8.0%, and preferably 1.5% to 7.0%.
[0065] [Fe: 10% to 30%] Fe is effective in improving the welding efficiency and arc concentration. If Fe is less than 10%, the welding efficiency decreases, and the arc spreads, causing the molten slag to be blown up. On the other hand, if Fe is more than 30%, iron grain protrusions are generated on the bead surface, deteriorating the bead appearance. Therefore, the Fe content is limited to 10% to 30%, and preferably 12% to 25%.
[0066] [Optional composition of flux] The above-mentioned chemical composition is the basic composition of the flux used in the present invention, but in addition to this basic composition, the present invention may further contain the following optional compositions as necessary. They are one or more selected from B2O3: 1.0% or less, K2O: 3.0% or less, Ti: 1.00% or less, and Al: 1.00% or less. Each will be explained individually below.
[0067] [Compound composition in optional composition of flux] [B2O3:1.0% or less] B2O3 is a component that contributes to improving the hardenability of the weld metal, but if it is contained in excess of 1.0%, it forms a low-melting liquid phase in the weld metal, inducing hot cracking. Therefore, the B2O3 content is preferably 1.0% or less. In order to obtain the effect of improving the hardenability of the weld metal, it is more preferable that the B2O3 content be 0.1% or more. More preferably, the content is 0.2% to 0.8%.
[0068] [K2O:3.0% or less] K2O is a component that stabilizes the arc during welding, but if it is contained in excess of 3.0%, it deteriorates moisture absorption resistance and increases the amount of diffusible hydrogen in the weld metal, inducing low-temperature cracking. Therefore, the K2O content is preferably 3.0% or less. In order to obtain the effect of stabilization during welding, it is more preferable to contain 1.0% or more. More preferably, it is 1.0% to 2.0%.
[0069] [Metal composition in optional composition of flux] [Ti:1.00% or less] Ti is added as metallic Ti, Fe-Ti, etc., and acts as a strong deoxidizer, reducing the amount of oxygen in the weld metal and contributing to improving toughness, but if it is contained in excess of 1.00%, the amount of solid-solubilized Ti in the weld metal increases, deteriorating toughness. Therefore, the Ti content is preferably 1.00% or less. In order to obtain the toughness improving effect, it is more preferable to contain it at 0.10% or more. It is further preferably 0.20% to 0.90%.
[0070] [Al: 1.00% or less] Al is added as metallic Al, Fe-Al, etc., and acts as a strong deoxidizer, reducing the amount of oxygen in the weld metal and contributing to improving toughness, but if it is contained in excess of 1.00%, the amount of solid-solubilized Al in the weld metal increases, deteriorating toughness. Therefore, the Al content is preferably 1.00% or less. In order to obtain the toughness improving effect, it is more preferable to contain 0.10% or more. More preferably, it is 0.20% to 0.90%.
[0071] [Remainder of flux composition] The remaining components contained in the flux other than those mentioned above are unavoidable impurities such as Ba, Li, P, and S. Of these unavoidable impurities, Ba and Li are each preferably limited to 3.0% or less, and in particular, P and S, which affect the welding quality, are each preferably limited to 0.1% or less.
[0072] [Flux alpha] As described above, when the CeqW of the welding wire is limited to 0.80 or less, the hardenability of the weld metal is insufficient in combination with the flux of the conventional technology, and the required weld metal strength cannot be met. In response to this, the inventors of the present invention have considered that it is effective to add an element effective for improving the hardenability of the weld metal from the flux, and have produced various fluxes and conducted intensive research. As a result, it has been found that the transfer of elements from the flux to the weld metal is influenced by the amount of elements added to the flux that improve the hardenability of Si, Mn, Ni, Cr, and Mo, as well as the amount of Fe in the flux. Furthermore, it has been found that it is possible to ensure both the strength of the weld metal and the crack resistance by adjusting α, which is expressed by the following formula (2) that shows the CeqW of each element added to the flux and the welding wire, to 0.35 to 0.70. α = (0.3-[Fe] F / 200)×{[Si] F / 24+[Mn] F / 6+[Ni] F / 40+[Cr] F / 5+[Mo] F / 4}+0.4×CeqW ··· (2) Here, the [components] of the flux in the above formula (2) F indicates the content (mass%) of the metal component, and is set to 0 if the component is not contained.
[0073] If this α is less than 0.35, the strength of the weld metal will be insufficient, and if it exceeds 0.70, welding defects (cracks) may occur. Therefore, α is limited to 0.35 to 0.70, and preferably 0.40 to 0.65.
[0074] [Weld metal] The above-mentioned 780 MPa class steel is butted together and submerged arc welding is performed using a welding wire and flux with a heat input of 300 kJ / cm or more, and the weld metal of the obtained weld joint has the chemical composition described below.
[0075] As a result, the mechanical properties of the weld metal without any welding defects, namely, a 0.2% yield strength of 630 MPa or more and a tensile strength of 780 MPa or more, were obtained, and the absorbed energy of the V-notch Charpy impact test at 0°C was v E0 can secure 27J or more.
[0076] The basic chemical composition of the weld metal is preferably as follows: C: 0.04% to 0.10%, Si: 0.10% to 0.80%, Mn: 0.9% to 2.0%, P: 0.015% or less, S: 0.015% or less, Ni: 1.6% to 5.0%, Cr: 0.3% to 2.0%, Mo: 0.5% to 2.0%, O: 0.040% or less, N: 0.010% or less. The balance is Fe and unavoidable impurities. In the composition, "%" means "mass %".
[0077] Furthermore, CeqD represented by the following formula (3) is preferably 0.75 to 0.95. CeqD=[C] D +[Si] D / 24+[Mn] D / 6+[Ni] D / 40+[Cr] D / 5+[Mo] D / 4 ··· (3) Here, the [elements] of the weld metal in formula (3) D indicates the content (mass%) of the element, and if the element is not contained, it is set to 0.
[0078] Furthermore, in addition to the basic composition of the weld metal, the following optional compositions may be contained as necessary: one or more selected from Cu: 1.0% or less, Al: 0.12% or less, Ti: 0.12% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.010% or less, and REM: 0.020% or less. Each of these will be explained individually below.
[0079] [Basic composition of weld metal] [C:0.04%~0.10%] C is an element that improves the strength of the weld metal. If the C content is less than 0.04%, the weld metal strength is insufficient. On the other hand, if the C content exceeds 0.10%, a hard second phase is formed in the weld metal, and the toughness is deteriorated. Therefore, the C content is preferably in the range of 0.04% to 0.10%, and more preferably 0.05% to 0.08%.
[0080] [Si:0.10%~0.80%] Silicon acts as a deoxidizing element in the weld metal and reduces the amount of dissolved oxygen, thereby contributing to improving the toughness of the weld metal. Silicon also has the effect of increasing strength by lowering the transformation temperature. If the silicon content is less than 0.10%, this effect is insufficient, and if it exceeds 0.80%, it promotes the formation of a hard second phase in the weld metal, deteriorating the toughness. Therefore, the silicon content is preferably in the range of 0.10% to 0.80%, and more preferably 0.20% to 0.60%.
[0081] [Mn: 0.9%~2.0%] Mn is an element that enhances hardenability, and in order to ensure the strength of the weld metal, it is preferable to contain 0.9% or more. On the other hand, since it is an element that is prone to solidification segregation, if it exceeds 2.0%, it will induce hot cracking due to solidification segregation. Therefore, Mn is preferably in the range of 0.9% to 2.0%, and more preferably 1.2% to 1.8%.
[0082] [P:0.015% or less] P is an element that segregates at grain boundaries in the weld metal and induces hot cracking, so it is preferable to reduce it as much as possible, but 0.015% or less is acceptable. Therefore, P is preferably in the range of 0.015% or less. Note that excessive reduction leads to an increase in refining costs for manufacturing the welding wire, so P is preferably adjusted to 0.003% or more, and more preferably 0.004% to 0.012%.
[0083] [S:0.015% or less] S is an element that segregates at grain boundaries in the weld metal and induces hot cracking, so it is preferable to reduce it as much as possible, but 0.015% or less is acceptable. Therefore, S is preferably in the range of 0.015% or less. Note that excessive reduction leads to an increase in refining costs for manufacturing welding wire, so S is preferably adjusted to 0.002% or more, and more preferably 0.003% to 0.012%.
[0084] [Ni: 1.6%~5.0%] Ni is an effective element in increasing the strength of weld metal without reducing toughness. To obtain this effect, Ni is preferably contained in an amount of 1.6% or more. On the other hand, Ni is an austenite stabilizing element, and when added in an amount exceeding 5.0%, the solidification primary crystals become austenite phase, which increases solidification segregation and induces hot cracking. Therefore, Ni is preferably in the range of 1.6% to 5.0%. More preferably, it is 2.0% to 4.5%.
[0085] [Cr: 0.3%~2.0%] Cr is an element that improves the strength of the weld metal. Such an effect becomes significant when the content is 0.3% or more. On the other hand, if the content exceeds 2.0%, the weld metal becomes hard, which reduces the toughness. Therefore, the Cr content is preferably in the range of 0.3% to 2.0%, and more preferably 0.4% to 1.8%.
[0086] [Mo: 0.5%~2.0%] Mo is an element that improves the strength of the weld metal. Such an effect becomes significant when the content is 0.5% or more. On the other hand, if the content exceeds 2.0%, the weld metal becomes hard, which reduces the toughness. Therefore, Mo is preferably in the range of 0.5% to 2.0%, and more preferably 0.6% to 1.6%.
[0087] [O:0.040% or less] O (oxygen) is an unavoidable impurity that reduces the toughness of the weld metal by forming oxides. Therefore, it is preferable to reduce the O content as much as possible, but since an O content of 0.040% or less is acceptable, it is preferable to keep it in the range of 0.040% or less. More preferably, it is 0.010% to 0.036%.
[0088] [N:0.010% or less] N (nitrogen) is an unavoidable impurity that deteriorates the toughness of the weld metal. Therefore, it is preferable to reduce the N content as much as possible, but it is acceptable if it is 0.010% or less. Therefore, N is preferably in the range of 0.010% or less. More preferably, it is 0.002% to 0.008%.
[0089] [Optional composition of weld metal] The above-mentioned chemical composition is the basic composition of the weld metal of the present invention, and in addition to this basic composition, the present invention may further contain the following optional compositions as necessary. These are one or more selected from Cu: 1.0% or less, Al: 0.12% or less, Ti: 0.12% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.010% or less, and REM: 0.020% or less. Each will be explained individually below.
[0090] [Cu:1.0% or less] Cu is an element that finely precipitates in the weld metal and improves strength through precipitation strengthening, but if it is contained in excess of 1.0%, it induces welding defects, so it is preferable to keep it in the range of 1.0% or less. Also, since the effect of improving the strength of the weld metal is significant at 0.1% or more, it is more preferable that it is 0.1% to 1.0%.
[0091] [Al: 0.12% or less] Al acts as a deoxidizing element in the weld metal, and reduces the amount of dissolved oxygen, thereby reducing oxides and contributing to high toughness of the weld metal. However, if it exceeds 0.12%, it forms coarse Al2O3 in the weld metal, which becomes the starting point of fracture. Therefore, it is preferable to keep it in the range of 0.12% or less. In order to obtain the effect of high toughness of the weld metal, it is preferable to contain 0.01% or more, and more preferably, it is 0.01% to 0.12%.
[0092] [Ti:0.12% or less] Ti acts as a deoxidizing element in the weld metal and reduces the amount of dissolved oxygen. It also reduces the interfacial energy between oxides and molten steel, finely dispersing the oxides and contributing to improving the toughness of the weld metal. However, if it exceeds 0.12%, the amount of dissolved Ti in the weld metal increases, decreasing ductility and toughness. Therefore, it is preferable to keep it in the range of 0.12% or less. In order to obtain such a toughness improving effect, it is preferable to contain Ti at 0.01% or more, and more preferably 0.01% to 0.12%.
[0093] [Nb:0.10% or less] Nb is an element that improves hardenability and contributes to improving the strength of the weld metal, but if it is contained in excess of 0.10%, it hardens the weld metal, reducing its toughness. Therefore, the Nb content is preferably in the range of 0.10% or less. In order to obtain the effect of improving the strength of the weld metal, it is preferable that Nb is contained in an amount of 0.01% or more, and more preferably, the Nb content is 0.01% to 0.10%.
[0094] [V:0.10% or less] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides in the weld metal. However, if it is contained in an amount exceeding 0.10%, it hardens the weld metal, and the toughness decreases. Therefore, it is preferable that the V content is in the range of 0.10% or less. In order to obtain such an effect of improving the strength of the weld metal, it is preferable that the V content is 0.01% or more, and more preferably, 0.01% to 0.10%.
[0095] [Ca:0.006% or less] Ca combines with S to form sulfide (CaS), thereby suppressing hot cracking. However, if it is contained in an amount exceeding 0.006%, it segregates at the prior austenite grain boundaries, embrittling the grain boundaries and reducing the toughness of the weld metal. Therefore, when Ca is contained, it is preferable that the content be in the range of 0.006% or less. In addition, such a hot crack suppression effect becomes significant when the Ca content is 0.001% or more, so the Ca content is more preferably 0.001% to 0.006%.
[0096] [B:0.010% or less] B is an element that enhances hardenability and contributes to improving the strength of the weld metal. However, if it is contained in an amount exceeding 0.010%, it induces hot cracking. Therefore, when B is contained, it is preferable that the content be in the range of 0.010% or less. In order to obtain such a strength improving effect, it is preferable that B is contained in an amount of 0.001% or more, and more preferably, it is 0.001% to 0.010%.
[0097] [REM:0.020% or less] REM combines with S in the molten metal to form sulfides with high melting points, suppressing the formation of sulfides with low melting points and contributing to the suppression of hot cracking. However, if the content exceeds 0.020%, it segregates at the prior austenite grain boundaries and acts to embrittle the grain boundaries, thereby reducing the toughness of the weld metal. Therefore, when REM is contained, it is preferable to keep it in the range of 0.020% or less. In addition, such a hot crack suppression effect becomes significant when the REM content is 0.002% or more, so it is more preferable that the content is 0.002% to 0.020%.
[0098] [Remainder of weld metal composition] The remaining composition other than the above-mentioned composition is composed of Fe and inevitable impurities. Examples of inevitable impurities include Sn, Sb, As, Pb, and Bi. It is preferable that the contents of Sn, Sb, and As in the weld metal are each 0.005% or less, and the contents of Pb and Bi are each 0.0001% or less. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, the inclusion of inevitable impurity elements other than these is not prevented, and such embodiments are also included in the technical scope of the present invention.
[0099] [Weld metal CeqD] Furthermore, in a submerged arc welding method with a heat input of 300 kJ / cm or more, in order to prevent the occurrence of welding defects while ensuring the strength and toughness of the weld metal, it is effective to adjust the CeqD of the weld metal, represented by the following formula (3), to 0.75 to 0.95. CeqD=[C] D +[Si] D / 24+[Mn] D / 6+[Ni] D / 40+[Cr] D / 5+[Mo] D / 4 ··· (3) Here, the [elements] of the weld metal in formula (3) D indicates the content (mass%) of the element, and if the element is not contained, it is set to 0.
[0100] The reason why the CeqD of the weld metal is set to 0.75 or more is to ensure the strength of the weld metal, but if the CeqD exceeds 0.95, the toughness decreases and the tendency for low-temperature cracking to occur increases.
[0101] [780MPa class steel] The base material (steel plate) of the present invention is a 780 MPa class steel. That is, the tensile strength is 780 MPa to 930 MPa. The manufacturing method of the 780 MPa class steel includes a method in which a steel material obtained through a conventional steelmaking process and casting process is hot-rolled by adjusting the heating conditions and rolling reduction, and then cooled to obtain a steel plate (steel material). The thickness of the steel plate after rolling is, for example, 40 mm to 100 mm.
[0102] The chemical composition of 780 MPa class steel is, for example, as follows: C: 0.03% to 0.15%, Si: 0.02% to 0.80%, Mn: 1.0% to 2.5%, P: 0.015% or less, S: 0.012% or less, Ni: 3.0% or less, Cr: 2.0% or less, Mo: 1.5% or less, N: 0.010% or less, O: 0.010% or less, balance: Fe and unavoidable impurities. In addition, the following optional compositions may be contained as necessary.
[0103] One or more selected from Cu: 1.0% or less, Al: 0.10% or less, Ti: 0.10% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.005% or less, and REM: 0.050% or less.
[0104] [Basic composition of steel plate] The basic composition of the 780 MPa class steel to be welded in the present invention will be described.
[0105] [C:0.03%~0.15%] C is an element that improves the strength of steel. To obtain this effect, a C content of 0.03% or more is necessary. On the other hand, if the C content exceeds 0.15%, a hard second phase is formed in the weld heat affected zone, decreasing toughness. For this reason, the C content is preferably in the range of 0.03% to 0.15%, and more preferably 0.04% to 0.12%.
[0106] [Si:0.02%~0.80%] Silicon acts as a deoxidizer and is an element that dissolves in steel and contributes to increasing the strength of the steel material through solid solution strengthening. To obtain such an effect, a content of 0.02% or more is required. On the other hand, if the content exceeds 0.80%, a hard second phase is formed in the weld heat affected zone, reducing toughness. For this reason, the content of silicon is preferably in the range of 0.02% to 0.80%, and more preferably 0.06% to 0.60%.
[0107] [Mn: 1.0%~2.5%] Mn is an element that enhances hardenability and contributes to ensuring the strength of steel. To obtain this effect, a content of 1.0% or more is required. On the other hand, since Mn is an element that is prone to solidification segregation, if the content exceeds 2.5%, excessive Mn will segregate in the center of the plate thickness, reducing toughness. For this reason, Mn is preferably in the range of 1.0% to 2.5%, and more preferably 1.2% to 2.0%.
[0108] [P:0.015% or less] P is an element that segregates to grain boundaries as an impurity and reduces toughness, and is preferably reduced as much as possible, but 0.015% or less is acceptable. For this reason, P is preferably set to a range of 0.015% or less. However, excessive reduction leads to high refining costs, so P is preferably adjusted to 0.003% or more. More preferably, it is 0.004% to 0.012%.
[0109] [S:0.012% or less] S exists as sulfide-based inclusions in steel, and reduces the ductility and cryogenic toughness of the steel material. For this reason, it is preferable to reduce S as much as possible, but 0.012% or less is acceptable. For this reason, S is preferably 0.012% or less. On the other hand, to extremely reduce S to less than 0.002%, a long refining time is required, and the refining cost increases. For this reason, from the viewpoint of economy, S is more preferably in the range of 0.002% or more. More preferably, it is 0.002% to 0.010%.
[0110] [Ni:3.0% or less] Ni is an effective element for improving the strength of steel without reducing its toughness. To obtain such an effect, it is preferable to contain 0.1% or more. On the other hand, if Ni exceeds 3.0%, cracks will occur during rolling, so Ni is preferably 3.0% or less. More preferably, it is 0.2% to 2.5%.
[0111] [Cr:2.0% or less] Cr is an element effective in improving the strength of steel materials. To obtain such an effect, it is preferable to contain 0.1% or more of Cr. On the other hand, if it is contained in excess of 2.0%, the grain size becomes coarse and the toughness decreases. For this reason, the Cr content is more preferably 0.2% to 1.8%.
[0112] [Mo: 1.5% or less] Mo is an element that contributes to improving the strength of steel materials. It also suppresses the formation of coarse structures formed from prior austenite grain boundaries, and contributes to improving toughness. To obtain such effects, it is preferable to contain Mo at 0.1% or more. On the other hand, if it is contained at more than 1.5%, carbides are formed in the weld heat affected zone, and toughness decreases. For this reason, Mo is preferably 1.5% or less. More preferably, it is 0.2% to 1.2%.
[0113] [N:0.010% or less] N is an unavoidable impurity that deteriorates the toughness of steel. Therefore, it is preferable to reduce the N content as much as possible, but it is acceptable if it is 0.010% or less. Therefore, N is preferably in the range of 0.010% or less, and more preferably 0.002% to 0.008%.
[0114] [O (oxygen): 0.010% or less] O (oxygen) exists as oxide-based inclusions in steel and reduces the cryogenic toughness of the steel material. For this reason, it is preferable to reduce O (oxygen) as much as possible, but 0.010% or less is acceptable. For this reason, O (oxygen) is preferably contained at 0.010% or less. Furthermore, in order to extremely reduce O (oxygen) to less than 0.001%, refining is required for a long time, and refining costs rise. For this reason, from the viewpoint of economy, O (oxygen) is more preferably 0.001% or more. More preferably, it is 0.002% to 0.008%.
[0115] [Optional composition of steel plate] The above-mentioned components are the basic composition of the steel sheet, but in addition to this basic composition, the steel sheet may contain the following optional components as necessary: one or more selected from Cu: 1.0% or less, Al: 0.10% or less, Ti: 0.10% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.005% or less, and REM: 0.050% or less.
[0116] [Cu:1.0% or less] Cu is an element that contributes to increasing the strength of steel through precipitation strengthening. However, if the content exceeds 1.0%, the weldability decreases and defects are likely to occur during the production of the steel. Therefore, when Cu is contained, it is preferable that the Cu content is in the range of 1.0% or less. In order to ensure the strength improvement effect, it is more preferable that the Cu content is 0.1% or more. More preferably, it is 0.2% to 0.8%.
[0117] [Al: 0.10% or less] Al acts as a deoxidizer and is the most commonly used element in the molten steel deoxidation process. However, if it is contained in excess of 0.10%, the crystal grains become coarse and the toughness is reduced. For this reason, the Al content is preferably in the range of 0.10% or less. In order to obtain the effect of improving toughness, it is more preferable to contain 0.01% or more. More preferably, it is 0.02% to 0.08%.
[0118] [Ti:0.10% or less] Ti forms TiN in steel, and TiN has the effect of suppressing austenite grain growth. In order to obtain such an effect, a Ti content of 0.01% or more is required. On the other hand, if the Ti content exceeds 0.10%, the toughness is reduced due to the solid solution Ti, so the Ti content is preferably 0.10% or less. More preferably, the Ti content is 0.01% to 0.08%. Further preferably, the Ti content is 0.02% to 0.06%.
[0119] [Nb:0.10% or less] Nb is an element effective in improving the strength of steel materials, and in order to obtain such an effect, a content of 0.01% or more is required. On the other hand, if the content exceeds 0.10%, carbides are precipitated and the toughness is reduced, so the content is preferably 0.10% or less. More preferably, it is 0.01% to 0.08%. Further preferably, it is 0.02% to 0.05%.
[0120] [V:0.10% or less] V is an element that precipitates fine carbides and contributes to improving the strength of steel materials. However, if the V content exceeds 0.10%, the steel will harden and the toughness will decrease. Therefore, if V is contained, it is preferable that the V content is 0.10% or less. In order to obtain the effect of improving the strength and toughness, it is more preferable that the V content is 0.01% or more. More preferably, it is 0.02% to 0.08%.
[0121] [Ca:0.006% or less] Ca is an element that precipitates spherical sulfides and contributes to preventing lamellar tearing. It is also an element that is effective in improving toughness. To obtain such effects, Ca needs to be contained in an amount of 0.001% or more. On the other hand, if it is contained in an amount exceeding 0.006%, it segregates at the prior austenite grain boundaries, reducing toughness. For this reason, Ca is more preferably in the range of 0.001% to 0.006%, and even more preferably 0.002% to 0.005%.
[0122] [B: 0.005% or less] B is an element that contributes to improving the toughness of steel by segregating at grain boundaries and suppressing the formation of coarse structures at the grain boundaries. However, if B is contained in an amount exceeding 0.005%, a hard martensite structure is formed, resulting in a decrease in toughness. Therefore, if B is contained, it is preferable that the B content is in the range of 0.005% or less. In order to obtain the effect of improving toughness, it is more preferable that B is contained in an amount of 0.001% or more. More preferably, it is 0.002% to 0.004%.
[0123] [REM:0.050% or less] REM is an element that has the effect of improving the toughness of steel material, and further improving ductility and resistance to sulfide stress corrosion cracking through morphological control of inclusions. However, if it is contained in an amount exceeding 0.050%, it exhibits high-temperature brittleness and induces cracking during hot rolling. Therefore, when REM is contained, it is preferable that the REM content is in the range of 0.050% or less. In order to obtain the effect of improving toughness, it is more preferable that the REM content is 0.002% or more. More preferably, the content is 0.010% to 0.040%.
[0124] [Remaining composition] The remaining composition other than the above-mentioned components is composed of Fe and inevitable impurities. Examples of the inevitable impurities include Mg, Sb, Bi, etc., and a total of 0.02% or less is acceptable. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, the inclusion of inevitable impurity elements other than these is not precluded, and such embodiments are also included in the technical scope of the present invention. EXAMPLES
[0125] The effects of the present invention will be specifically described below with reference to examples and comparative examples. The steel plates prepared were 780 MPa class steel having the thickness and composition shown in Table 1, and a V-groove with a groove angle of 35° was formed.
[0126] [Table 1]
[0127] The welding wire was prepared by melting molten steel having the composition shown in Table 2 in a vacuum melting furnace and casting it into a 300 kg steel ingot. The obtained steel ingot was heated to 1000°C, and then hot-rolled and cold-rolled to produce a welding wire having a diameter of 6.4 mm.
[0128] [Table 2]
[0129] The flux was prepared by compounding the raw material powders so as to obtain the composition shown in Table 3, kneading them with a binder (water glass), granulating them, and firing them at 500°C. The granulated flux was subjected to a granulation process, including removing dust and crushing coarse particles, to adjust the particle size of all particles to 2.5 mm or less.
[0130] [Table 3]
[0131] Using the steel plates, welding wire, and flux, submerged arc welding was performed under the welding conditions shown in Table 4 to produce submerged arc welded joints.
[0132] [Table 4]
[0133] After welding, a test piece was taken from the center of the weld metal and subjected to elemental analysis by wet analysis. In addition, the cross-section of the welded joint was observed under an optical microscope to determine whether or not there was a weld defect. If a weld defect was found in the weld, it was rated as "present." If no weld defect was found, it was rated as "absent."
[0134] [Measurement of mechanical properties of weld metal] Tensile test pieces (parallel portion diameter: 10 mmφ) and Charpy impact test pieces (V notch) were taken from the obtained weld metal in accordance with the provisions of JIS Z 3111, and tensile tests and impact tests were carried out.
[0135] The tensile test was carried out at room temperature on three pieces of each wire, and the average of the obtained values (0.2% proof stress) was regarded as the tensile property of the weld metal using the wire.
[0136] In addition, Charpy impact tests were performed on three specimens each, and the absorbed energy ( V E0) was calculated, and the average value was regarded as the low-temperature impact toughness of the weld metal using the wire. The V-notch position of the Charpy impact test piece was set at the center of the weld metal, which is half the plate thickness.
[0137] The results obtained are shown in Table 5.
[0138] [Table 5]
[0139] In all of the examples of the present invention, no welding defects were observed. Furthermore, the yield strength (0.2% proof stress) at room temperature was 630 MPa or more, the tensile strength was 780 MPa or more, and the absorbed energy in the Charpy impact test at a test temperature of 0°C was V The welded joints had high strength and excellent toughness, with E0 of 27J or more.
[0140] On the other hand, in the comparative examples outside the scope of the present invention, the desired welded joints could not be obtained due to the occurrence of welding defects or insufficient impact toughness of the weld metal.
Claims
1. In a submerged arc welding method for 780 MPa class steel with a welding heat input of 300 kJ / cm or more, The chemical composition of the welding wire used is, in mass%, C: 0.03% to 0.12%, Si: 0.01% to 0.60%, Mn: 1.0% to 2.0%, P: 0.015% or less, S: 0.015% or less, Ni: 1.0% to 4.0%, Cr: 1.5% or less, Mo: 0.2% to 1.2%, O: 0.015% or less, N: 0.010% or less, The balance is Fe and unavoidable impurities. CeqW represented by the following formula (1) is in the range of 0.40 to 0.80, The composition of the flux used is, in mass%, Yes 2 :5%~30%, CaO: 1% to 10%, MgO: 5% to 30%, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :33%~220%、 TO 2 :2%~20%、 Na 2 O:1%~3%、 CaF 2 :2%~20%、 One or more metal carbonates 2 Total conversion value: 2% to 12% Si: 0.10% to 2.50%, Mn: 0.1% to 2.0%, Ni: 1.0% to 12.0%, Cr: 8.0% or less, Mo: 1.0% to 8.0%, Fe: 10% to 30%, and the remainder being unavoidable impurities, The value of α represented by the following formula (2) is in the range of 0.35 to 0.
70. A submerged arc welding method comprising: CeoW=[C] W +[Yes] W / 24+[M] W / 6+[N] W / 40+[C] W / 5+[] W / 4 ・・・ (1) α=(0.3-[Fe] F / 200)×{[Si] F / 24+[Mn] F / 6+[Ni] F / 40+[Cr] F / 5+[Mo] F / 4}+0.4×CeqW ・・・ (2) Here, the [elements] of the wire in the above formula (1) W Or the [component] of the flux in the above formula (2) F indicates the content (mass%) of the element or component, and is set to 0 when the element or component is not contained.
2. In addition to the chemical composition of the welding wire, further, in mass%, Cu: 1.0% or less, Al: 0.20% or less, Ti: 0.20% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.010% or less, B: 0.010% or less, REM: 0.020% or less 2. The method according to claim 1, further comprising the step of:
3. In addition to the component composition of the flux, the following is further included in mass%: B 2 O 3 : 1.0% or less, K 2 O:3.0% or less, Ti: 1.00% or less, Al: 1.00% or less 3. The submerged arc welding method according to claim 1, further comprising one or more selected from the group consisting of:
4. A method for producing a welded joint, comprising the steps of: producing the welded joint by using the submerged arc welding method according to claim 1 or 2;
5. A method for producing a welded joint, comprising the steps of: producing the welded joint by using the submerged arc welding method according to claim 3;
6. The chemical composition of the weld metal of the weld joint is, in mass%, C: 0.04% to 0.10%, Si: 0.10% to 0.80%, Mn: 0.9% to 2.0%, P: 0.015% or less, S: 0.015% or less, Ni: 1.6% to 5.0%, Cr: 0.3% to 2.0%, Mo: 0.5% to 2.0%, O: 0.040% or less, N: 0.010% or less, The balance is Fe and unavoidable impurities. CeqD represented by the following formula (3) is 0.75 to 0.95 The method for manufacturing a welded joint according to claim 4. CeoD=[C] D +[Yes] D / 24+[M] D / 6+[N] D / 40+[C] D / 5+[] D / 4 ・・・ (3) Here, the [elements] of the weld metal in formula (3) D represents the content (mass%) of the element, and is set to 0 when the element is not contained.
7. The composition of the weld metal of the weld joint is, in mass%, C: 0.04% to 0.10%, Si: 0.10% to 0.80%, Mn: 0.9% to 2.0%, P: 0.015% or less, S: 0.015% or less, Ni: 1.6% to 5.0%, Cr: 0.3% to 2.0%, Mo: 0.5% to 2.0%, O: 0.040% or less, N: 0.010% or less, The balance is Fe and unavoidable impurities. CeqD represented by the following formula (3) is 0.75 to 0.95 The method for manufacturing a welded joint according to claim 5 . CeoD=[C] D +[Yes] D / 24+[M] D / 6+[N] D / 40+[C] D / 5+[] D / 4 ・・・ (3) Here, the [elements] of the weld metal in formula (3) D represents the content (mass%) of the element, and is set to 0 when the element is not contained.
8. In addition to the chemical composition of the weld metal of the weld joint, Cu: 1.0% or less, Al: 0.12% or less, Ti: 0.12% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.010% or less, REM: 0.020% or less 7. The method for manufacturing a welded joint according to claim 6, characterized in that the welded joint contains one or more selected from the following:
9. In addition to the chemical composition of the weld metal of the weld joint, Cu: 1.0% or less, Al: 0.12% or less, Ti: 0.12% or less, Nb: 0.10% or less, V: 0.10% or less, Ca: 0.006% or less, B: 0.010% or less, REM: 0.020% or less 8. The method for manufacturing a welded joint according to claim 7, characterized in that it contains one or more selected from the following:
10. The mechanical properties of the weld metal of the weld joint are that the yield strength (0.2% proof stress) at room temperature is 630 MPa or more, the tensile strength of the weld metal is 780 MPa or more, and the absorbed energy of the V-notch Charpy impact test at a test temperature of 0°C is V E 0 The method for manufacturing a welded joint according to claim 6, characterized in that the strength is 27 J or more.
11. The mechanical properties of the weld metal of the weld joint are that the yield strength (0.2% proof stress) at room temperature is 630 MPa or more, the tensile strength of the weld metal is 780 MPa or more, and the absorbed energy of the V-notch Charpy impact test at a test temperature of 0°C is V E 0 The method for manufacturing a welded joint according to claim 7, characterized in that the strength is 27 J or more.
12. The mechanical properties of the weld metal of the weld joint are that the yield strength (0.2% proof stress) at room temperature is 630 MPa or more, the tensile strength of the weld metal is 780 MPa or more, and the absorbed energy of the V-notch Charpy impact test at a test temperature of 0°C is V E 0 The method for manufacturing a welded joint according to claim 8, characterized in that the strength is 27 J or more.
13. The mechanical properties of the weld metal of the weld joint are that the yield strength (0.2% proof stress) at room temperature is 630 MPa or more, the tensile strength of the weld metal is 780 MPa or more, and the absorbed energy of the V-notch Charpy impact test at a test temperature of 0°C is V E 0 The method for manufacturing a welded joint according to claim 9, characterized in that the weld strength is 27 J or more.
Citation Information
Patent Citations
Wire for submerged arc welding of high-tensile steel
JP2004337863A
Two electrode type heavy heat input submerged arc welding method
JP2005271045A
Submerged arc weld metal of high tensile strength steel
JP2007260696A
High strength welded steel pipe having weld metal excellent in low temperature crack resistance, and its manufacturing method
JP2008240096A
Solid wire for submerged arc welding
JP2015110241A